Hysteroscopy versus transvaginal ultrasonography: finding the better modality for evaluation of postmenopausal bleeding - Bhoj, Mishika; Yadav, Shakti Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The most common cause of postmenopausal bleeding is benign pathology, but likelihood of malignancy must be promptly excluded. As excision of localized lesion has higher disease-free survival rate and lower morbidity as opposed to treatment for regional-stage disease. Commonly employed blind dilatation and curettage followed by histopathology is the current standard. A screening method with high sensitivity and specificity can help to prevent the invasive procedure and can also improve the accuracy of the biopsy. The objective of the present study was to study and compare the diagnostic accuracy of hysteroscopy and transvaginal ultrasonography in diagnosis of postmenopausal bleeding. Methods: 80 female patients with complaints of postmenopausal bleeding were enrolled and followed up for a period of 10 months. Each patient underwent transvaginal ultrasonography and hysteroscopy followed by endometrial biopsy. Result were analyzed to find sensitivity, specificity, accuracy, PPV and NPV taking histopathological diagnosis as gold standard. Results: Authors found that in 40 patients (50%), the cause of post-menopausal bleeding was caused atrophic endometrium followed by endometrial hyperplasia seen in 14 patients (17.5%). Hysteroscopy had higher overall sensitivity, specificity, NPV and accuracy as compared to transvaginal ultrasonography. Hysteroscopy was found to be highly accurate in diagnosing endometrial carcinoma (100%) and endometrial polyps (100%). However, both methods showed similar accuracy (97.5%) in diagnosis of proliferative endometrium and hyperplasia. Conclusions: Hysteroscopy is comparable to histopathology and superior to transvaginal sonography in the diagnosis of intrauterine causes for postmenopausal bleeding, it also offers the possibility of visualizing macroscopic or focal intra-uterine abnormalities.